Sosialisasi Pembelajaran Berdiferensiasi untuk Memenuhi Kebutuhan Belajar Murid dalam Kurikulum Merdeka Belajar - Firinta Togatorop; Daulat Nathanael Banjarnahor; Doris Yolanda Saragih (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Independent Learning Curriculum Policy is an effort to transform education in Indonesia to produce graduates who have the Pancasila Student Profile. Independent learning gives schools, teachers and students the freedom to innovate and act in the teaching and learning process. Teachers are strongly advised to be creative in teaching and must side with the students to implement the independent learning. Differentiated learning is an effort to adapt the learning process in the classroom to have the learning needs of each individual. The implementation of differentiated learning needs to be carried out by following the principles in the Merdeka curriculum where learning is student-centered, and in accordance with interests and talents. The aim of implementing this service activity is to provide teachers with an understanding of differentiated learning in the Merdeka curriculum. This service activity was carried out at SMPS PARULIAN 1 Medan. The activity participants were the principal and teachers at the school. The form of activity is in the form of socialization by providing theory and preparing initial learning assessments as part of preparation for differentiated learning. The results of this service show that there is an increase in participants' understanding of differentiated learning which is in accordance with the principles of the Merdeka curriculum. Participants feel they understand differentiated learning which is oriented to students' interests and learning needs.